Anatomically Adaptive Coils for MRI—A 6-Channel Array for Knee Imaging at 1.5 Tesla - Gruber, Bernhard; Rehner, Robert; Laistler, Elmar; Zink, Stephan (Frontiers in Physics, 2020)
Purpose: Many of today’s MR coils are still somehow rigid and inflexible in their size and shape as they are intentionally designed to image a specific anatomical region and to fit a wide range of patients. Adaptive coils on the other hand, are intended to follow an one-size-fits-all approach, by fitting different shapes and sizes. Such coils improve the SNR for a wide range of subjects by an optimal fit to the anatomical region of interest, and in addition allow an increased handling and patient comfort as one MRI receive-coil is maintained instead of multiple. Material and Methods: To overcome the SNR losses by non-fitting and thus poorly loaded RF coils, we propose a stretchable antenna design. Each loop has the ability to reversibly stretch up to 100% of its original size, to be anatomically adaptive to different shapes and sizes, and therefore make the coil usable for a wide patient population. Besides the mechanical challenge to find a robust but flexible conductive material, various other problems like frequency and matching shifts affect the SNR. Through bench measurements and MR Imaging at 1.5T, we investigated different stretchable conductor materials, that fit the defined requirements. Finally, a rigid reference coil and an adaptive 6-channel array for knee imaging at 1.5 Tesla were developed to investigate the potential improvement in SNR. Results: The material tests identified two potentially useful materials: Highly ductile copper and a silver-plated stranded copper wire. Although, the adaptivity causes a frequency shift of the resonance frequency, which entails in variations of the impedance that each coil presents to its connected pre-amplifier, there are strategies to mitigate these effects. The adaptive array made of partly-stretchable loops, showed an improved SNR of up to 100% in 20 mm depth from the phantom surface, and therefore demonstrates the effectiveness of adaptive coils.